Christian responses to Roman art and architecture: the second-century church amid the spaces of empire - Nasrallah, Laura Salah (Cambridge Univ. Press, 2010)
Introduction -- Christian apologists and the second-century built environment -- Bringing together literature and archaeological remains -- Framing the question, framing the world -- What is an apology? : Christian apologies and the so-called Second Sophistic -- What does it mean to apologize? -- Addressing the Roman emperors, being Greek -- Defining the so-called Second Sophistic -- Traveling to Olympia : material manifestations of Greek Paideia and imperial address -- The Fountain of Regilla and Herodes Atticus -- Apologetics and christianness -- What is the space of the Roman Empire? : mapping, bodies, and knowledge in the Roman world -- Traveling men : Lucian, Tatian, and Justin -- Lucian -- Tatian -- Justin -- The Sebasteion in Aphrodisias -- Into the cities -- What informs the geographical imagination? : the Acts of the Apostles and Greek cities under Rome -- Placing Acts -- The Panhellenion -- Hadrian, ethnicity, and true religion -- What has Athens to do with Rome? -- Traveling back to Acts -- Acts 2 -- Paul in Lystra and Athens : confusing humans and gods -- Paul in Thessalonikē and Philippi : Roman sedition against Rome? -- What is justice? what is piety? what is Paideia : Justin, the forum of Trajan in Rome, and a crisis of mimēsis -- The column of Trajan -- Justin's apologies -- Names and deeds : Justin introduces himself, the emperors, and the mock court -- On the name -- The name and speech-acts -- A higher court -- Mimēsis, images, and daimones -- Sameness and difference -- Justice, piety, and Paideia in the Forum of Trajan -- The forum's surroundings -- Moving through the forum of Trajan -- War and the "temple of peace" -- Human bodies and the image(s) of god(s) -- How do you know God? : Athenagoras on names and images -- "This golden one, this Herakles, this God" : Commodus and Herakles -- The ambivalence of Herakles -- Commodus as Herakles -- A proliferation of signs -- Athenagoras -- Athenagoras's argument : the proemium -- Grammar and theology -- Atheism and piety "in the presence of philosopher-kings" -- The material gods -- What do we learn when we look? (part I) images, desire, and Tatian's to the Greeks -- What an image does -- The origins of images -- What you see and what you get : theorizing vision -- Images and the theological imagination : Cicero, Dio, and Maximus of Tyre -- Tatian, spectacle, and connoisseurship -- Tatian at the theater -- Tatian's grand tour -- What do we learn when we look? (part II) Aphrodite and Clement of Alexandria -- The Knidian Aphrodite and her afterlife -- Aphrodite at Knidos -- Pseudo-Lucian and the Knidia -- The Knidia and the ancient gaze -- The Knidia and Roman portraits -- Clement of Alexandria -- Alexandria, the mad, hybrid, spectacular city -- Introducing clement's Exhortation -- "They say a girl loved an image" : The exhortation on statues, piety, and desire -- Clement on the Knidian Aphrodite -- Stories of the gods : the pornographic Venus and Mars